Architettura e scultura romanica nel Contado del Seprio. Nuove considerazioni sul complemento plastico della chiesa monastica di Cairate - Cassanelli, Roberto (Hortus Artium Medievalium, 2014)
Abstract The recent conclusion of the archaeological investigations in the benedictine nunnery of Cairate (a small town between Milan and Varese in the valley of the Olona river) makes a decisive contribution to a better understanding of Romanesque art and architecture in the ‘Contado del Seprio’ (Seprio County, as then this territory was called), until very recent times neglected by scholars of medieval art, with the notable exception of the early medieval site of Castelseprio. The excavations have revealed the structures of the abbey church, a basilical plan ending with three apses, radically transformed in the second half of XVI century. It is now possible to try to replace, at least ideally, the sculptural fragments from the church preserved in various museums of Lombardy (Gallarate; Milan, Pinacoteca Ambrosiana and Castello Sforzesco). Variously dated from the eighth to the twelfth century, these fragments can now be certainly referred to the mid-twelfth century building, in connection to a large reconstruction project of the abbey church probably promoted by the bishop of Pavia and the nuns under the patronage of the emperor Frederick Barbarossa. Among these fragments stand out the three reliefs now in the Pinacoteca Ambrosiana, originally carved in the jambs of a portal, maybe representing ‘ancillae Dei’, consecrated virgins with a lamp waiting for Christ, the mystic groom, a theme present in the oldest liturgical drama known (the ‘Sponsus’).